Pemanfaatan Dana Program Keluarga Harapan terhadap Peningkatan Kesejahteraan Masyarakat di Kecamatan Rantau Selamat - Nurfadila Nurfadila (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
The problem that arose in the implementation of the Family Hope program in Rantau Selamat District was the lack of effectiveness in implementing PKH, where in the process of selecting people who would be given PKH assistance it was often not right on target in realizing the welfare of the people of Rantau Selamat District. This study aims to determine the utilization of the Family Hope Program (PKH) funds for the welfare of the people in Rantau Selamat District. The results of the study explain that in general the implementation and beneficiaries of PKH in Rantau Selamat District have been effective, but there are also PKH beneficiaries who use them for purposes whose categories have been determined by the government.